(untitled) (Sciental Journal of Education Humanities and Social Sciences, 2026)
This article analyzes handicrafts, which are considered one of the main types of traditional economy, in particular, aspects of home crafts that differ from other traditional types, ethno-local features characteristic of the Surkhan-Sherabad oasis, including types of home crafts that are widespread in the oasis, a unique division of labor in this area, raw materials of products and the process of their preparation.